2017
DOI: 10.1111/1541-4337.12258
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Contributing Factors to “Dark Cutting” Meat: Current Trends and Future Directions: A Review

Abstract: Dark cutting in beef and sheep meat has been the subject of extensive research with numerous associations established between it and various production practices. Despite these associations, dark cutting still occurs and causes significant financial losses globally in the fresh meat market. Consumers tend to reject dark meat as it is perceived to be from old or poorly-handled animals and is described as being tough, having an undesirable flavor, and having a short shelf-life. There is no universal system to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(130 citation statements)
references
References 358 publications
(502 reference statements)
5
109
1
15
Order By: Relevance
“…awed in-bag dry-aged beef in the current study became darker but still within the consumer acceptable range (approx. 35-40 of L * ) [54]. a * declined to around 13.0 which was slightly below the threshold of 14.5, according to their study.…”
Section: Effect Of Frozen Storage On Lean Dry-aged Beef For Differentmentioning
confidence: 80%
“…awed in-bag dry-aged beef in the current study became darker but still within the consumer acceptable range (approx. 35-40 of L * ) [54]. a * declined to around 13.0 which was slightly below the threshold of 14.5, according to their study.…”
Section: Effect Of Frozen Storage On Lean Dry-aged Beef For Differentmentioning
confidence: 80%
“…Furthermore, the reasons for the variance in both the biochemical parameters and the eating quality traits being attributable to intra‐animal variability under stress conditions are not entirely clear. For example, variability in the incidence of dark cutting meat in beef and sheep between animals of the same breed, maintained under the same diet and transported to the same abattoir, has been attributed to different handling practices and individual variability in stress susceptibility (Ponnampalam et al., ). Broilers subjected to preslaughter transport under high ambient temperature showed different activities of stress indicators, different protein profiles of the pectoralis major ( PM ) muscle, and variations in meat quality (Xing et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have reported the main factors contributing to dark cutting meat and the controversial use of pHu to detect it. [ 11 ] A high pHu meat is related to pre‐slaughter stress condition but not in all cases this gives rise to DFD meat. [ 12 ] The discovery of reliable protein biomarkers related to stress response in farm animals has been proposed to assist in better explain occurrence of defective meats.…”
Section: Introductionmentioning
confidence: 99%